A Cost-Benefit Analysis of Zero Trust Architecture (ZTA) Using Hybrid Financial Impact and Threat Mitigation Strategy (International Journal of Innovative Computing, 2026)
Zero Trust Architecture (ZTA) emerges as a pivotal cybersecurity paradigm, fundamentally shifting from traditional perimeter-based security models to a 'Never Trust, Always Verify' ethos, which necessitates continuous authentication and authorization for all network requests, regardless of origin. The increasing adoption of cloud technologies, Internet of Things (IoT) devices, and remote workforces has significantly expanded enterprise network perimeters, rendering conventional security methods such as Virtual Private Networks (VPNs) inadequate against modern attacks like Man-In-The-Middle and Denial of Service (DoS). Despite the growing recognition of ZTA's importance, organizations often exhibit hesitancy in committing resources due to a perceived lack of comprehensive quantitative data on its benefits, available tools, pricing structures, and efficacy rates. This research directly addresses this critical gap by conducting a rigorous cost-benefit analysis, evaluating the financial impact, cost-effectiveness, and threat mitigation outcomes of ZTA implementation. The study's methodology is structured in three phases. In Phase 1, ZTA tools, resources, and components were identified, along with the necessary investments. Vendor pricing data was collected from reputable security providers, including Microsoft, Kaspersky, IBM, CrowdStrike, Google, and BlackBerry. These vendors offer a wide range of security services such as Data Encryption, Identity and Access Management (IAM), Data Protection, Cloud Storage, and Micro-Segmentation. The selected tools and resources function as core threat mitigation strategies designed to reduce data breach risks and associated financial losses. Additionally, data-driven, quantitative methodologies are applied to estimate the total cost of implementing ZTA tools and resources.
Keywords: Zero-trust architecture, tools, cost effectiveness, cost and benefit analysis